A case study on manufacturing waste reduction through just in time - Mohd Rozaimi, Arshad (2007)
The waste reduction through JIT concept that can reduce cycle time is difficulty to find a good solution. However after make solution of this project and discuss with engineer have many constraint that cannot apply in reduce cycle time. In classify the waste that occur in production line of product 4900-X-319 is successful. This product have about 5 types of waste is defect product, motion, transportation, processing and waiting time. To collect this information some observation has to do and discuss with engineer. The cycle time from this product have to collect using stopwatch. The data have to measure at least 3 times because in engineering the accurate data is important. While collect the data each process of this product has to understand and this will give idea to provide a solution about reducing cycle time. After that make line balancing of 4900-X-319 and the total time to produce this product is 5.33minlpiece. To achieve last objective several solution have to discuss with engineer. The result of the solution has be reject because many constraint from factory that can implement in this product. If this solution acceptable the cycle time will reduce about 24s and can reduce operator cost.